MANAJEMEN PERUBAHAN DALAM ORGANISASI PENDIDIKAN - Martoatmodjo, Ganjar Winata (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Change management is a chain of activities through management process of cooperation from people who join in educational organization, to reach education goal, to become effective and efficient also resulting new matters such as policy, product, or new idea. There are individual resistance because of personality, perception and need, so that individual has potetential as refusal source to change. The matters which include in individual resistance are habit, secure, economical factor, unsure and perception. There are six refusal source to change. Organizational resistance have some aspects involve: 1) structural inertia; 2) broad impact of change; 3) group inertia; 4) expertise threat; 5) power threat; 6) resource allocation threat. Approachment in changing management of organization is classical approachment which assumed by Kurt Lewin that consists of three steps: First, Unfreezing the status quo; Second, Movement to the new state, Third, Refreezing the new change to make it permanent.